Alternative Calculations of Individual Patient Time in Therapeutic Range While Taking Warfarin: Results From the ROCKET AF Trial. Issue 3 (3rd March 2015) - Singer, Daniel E.; Hellkamp, Anne S.; Yuan, Zhong; Lokhnygina, Yuliya; Patel, Manesh R.; Piccini, Jonathan P.; Hankey, Graeme J.; Breithardt, Günter; Halperin, Jonathan L.; Becker, Richard C.; Hacke, Werner; Nessel, Christopher C.; et al.
Abstract : Background: In the ROCKET AF (Rivaroxaban–Once‐daily, oral, direct Factor Xa inhibition Compared with vitamin K antagonism for prevention of stroke and Embolism Trial in Atrial Fibrillation) trial, marked regional differences in control of warfarin anticoagulation, measured as the average individual patient time in the therapeutic range (iTTR) of the international normalized ratio (INR), were associated with longer inter‐INR test intervals. The standard Rosendaal approach can produce biased low estimates of TTR after an appropriate dose change if the follow‐up INR test interval is prolonged. We explored the effect of alternative calculations of TTR that more immediately account for dose changes on regional differences in mean iTTR in the ROCKET AF trial. Methods and Results: We used an INR imputation method that accounts for dose change. We compared group mean iTTR values between our dose change–based method with the standard Rosendaal method and determined that the differences between approaches depended on the balance of dose changes that produced in‐range INRs ("corrections") versus INRs that were out of range in the opposite direction ("overshoots"). In ROCKET AF, the overall mean iTTR of 55.2% (Rosendaal) increased up to 3.1% by using the dose change–based approach, depending on assumptions. However, large inter‐regional differences in anticoagulation control persisted. Conclusions: TTR, the standard measure of control of warfarin anticoagulation, depends on imputing daily INR values for the vast majority of follow‐up days. Our TTR calculation method may better reflect the impact of warfarin dose changes than the Rosendaal approach. In the ROCKET AF trial, this dose change–based approach led to a modest increase in overall mean iTTR but did not materially affect the large inter‐regional differences previously reported. Clinical Trial Registration: URL: ClinicalTrials.gov. Unique identifier: NCT00403767.